A proteção integral da primeira infância como instrumento assecuratório do direito ao desenvolvimento - Hiromoto, Carolina Magnani (2019)
The present thesis will develop the intertwining of two third generation fundamental rights, related to human solidarity, whose purpose is to provide means to human dignity, there are: the right to development and integral protection. The study will follow the analysis of international norms and homeland legislation regarding the right to development and Integral protection, as well as the public policy guidelines advocated by international organizations and local jurisprudence. It will be demonstrated that a person's right to development must be understood and promoted from birth to 18, with emphasis on early childhood. During childhood and adolescence, the individual goes through the greatest phase of transformation and formation, so the fundamental rights plexus must be satisfied from the perspective of the theory of integral protection and its informing principles: respect for the peculiar condition of the person in the process of development and absolute priority. The protection of the early childhood by the law with the respective public policy attainment announced in the legal norms can and should be a transforming instrument for the realization of fundamental rights leading to the evolution of their skills, competences and aptitudes to enjoy the rights of the first, second and third generations in childhood and adolescence as well in adulthood. Thus, the integral protection of early childhood is an instrument of assurance of the right to economic and social development, provided that there is participation of the actors of world society: states, corporations, organized civil society, multilateral organizations and the family. The Thesis is organized in such a way as to characterize fundamental and human rights, integral protection, early childhood, the right to development and aspects related to childhood, and the protection of early childhood as a tool to ensure the right to development